Peran Suami Sebagai Motivator Terhadap Kebutuhan Ibu Usia Subur Dalam Menggunakan Metode KB Suntik 1 Bulan Di BPM Farida Hajri Surabaya - Regina Putri Waromi, - (2020)
Back ground : Contraceptive is a method or tool used to prevent and control pregnancy. There are several types of contraception based on WUS's needs (women of child-bearing age), including one month-KB injection method. The success of one month-KB injection for WUS is influenced by several factors, one of which is the husband's role in meeting the needs of WUS due to the lack of the husband's role in fulfilling the needs of the wife's reproductive demands. In this case, the need to use contraception or family planning.This study focuses on the husband's role as a motivator to meet the needs of women of child-bearing age in using 1-month KB injections at BPM Farida Hajri Nyamplungan Surabaya. Method : This research adopts observational and crosses sectional analytic research methods. The sample of this research is mothers of child-bearing age who were present at the time of the study and included in the inclusion criteria. This study uses the total sampling technique and the chi-square test to analyze the variables. Result : as many as 51 respondents stated that the husband's role was lacking but the needs of the mother were met as many as 25 people (86.2%) and only 4 people (13.8) who stated the needs of the mother. while as many as 22 people (100%) stated that the husband's role was good and the mother's needs were fulfilled. Chi Square test results obtained p value 0.124 > α = 0.05, so there is no relationship between the husband's role as a motivator to the needs of women of childbearing age in using the 1 month injection contraceptive method. Conclusions : In this research, it was found that there was no relationship between the husband's role as a motivator in meeting the needs of mothers of childbearing age, whether the husband's role as a motivator was good or not, the mother's needs were still fulfilled.